A SEMANTIC ANALYSIS ON ED SHEERAN SONGS - IKA TRISNANTASARI; MUSTAMIN UMALEKHOA (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2017)
Semantic is the branches of linguistics. This branch is the important one, and there are lexical meaning and contextual meaning. By listening to the songs, we can get knowledge about appreciates literature and the background of the song. Therefore, the researcher was interested in analyzing the kinds of meaning used in Ed Sheeran songs. The researcher dedicated to give the title of this research Ã¢â‚¬Å“Semantic Analysis on Ed Sheeran SongsÃ¢â‚¬Â. The problem of this study is: (1) what are the lexical meanings in the Ed Sheeran Songs? (2) What are the contextual meaning in the Ed Sheeran Songs. The researcher takes five songs from different album. This study used a descriptive qualitative method because the researcher would analysis and interpret the research object of Ed Sheeran Songs. The step to obtain the data is by collecting sources of the data from Ed sheeran Songs and from internet. After that she selects the songs which contain of semantic, reads and listens to the lyrics to understand the content of the songs conducts and analyzes the collected data and makes conclusion.The result of this research is as follows: (1) related to the lexical meaning, while (2) related to the contextual meaning. The researcher expects this research will be useful for the other researchers who are eager to know more about semantics. Moreover, semantic is an important branch of linguistics that is interesting to be studied, especially when it is applied to literary works, such us songs or poem etc.Ã‚Â Key Words: Semantic, song, lexical meaning, contextual meaning, Ed Sheeran, word.